Molecular basis of nutrition and aging - Malavolta, Marco; Mocchegiani, Eugenio (Molecular nutrition series., 2016)
This volume synthesizes research on the underlying nutritional issues associated with aging, including the molecular, cellular, and systemic consequences of diet, nutrition, and health. It also explores the nutritional factors involved in aging, from the biomolecular level to individual health, including the effects of specific dietary compounds and interventions.